A Study of Relationship and Impact of Foreign Direct Investment on Economic Growth Rate of India - Sharil Sharma; Manpreet Kaur; Preeti Sharma; Sukhmani Sandhu (International Journal of Economics and Financial Issues, 2020)
One of the main pointers of the health of any economy is its Gross Domestic Product (GDP). It indicates the size of the economy. It also helps in determining and comparing the growth of economy over different periods and also with that of other economies. Investment is the major factor that contributes to the growth of GDP. Increase in level of investment leads to the multiplier impact on increasing the levels of employment and income. There is significant role of Foreign Investment in open economies. Such investment can be direct or indirect. The current study aims to know the relationship and impact of growth rate of foreign direct investment (FDI) in India on growth rate of GDP in India. The study used correlation analysis and regression analysis. It found that there existed insignificant relationship between the growth rate of FDI and economic growth rate. Also, the results of regression analysis indicated the no significant impact of growth rate of FDI on growth rate of GDP. Keywords: FDI, GDP, Economic growth, Indian economy JEL Classifications: E01, F21, F43 DOI: https://doi.org/10.32479/ijefi.10463